Dual-energy CT cisternography in the evaluation of CSF leaks: A novel approach - Alexandra M. Foust, DO (Radiology Case Reports, 2018)
Cerebrospinal fluid leaks pose a serious threat to patients as they represent an unchecked communication between the subarachnoid space and the extracranial environment. Accurate localization of the leakage site is essential for treatment planning. We describe the novel utilization of dual-energy computed tomography technology in cisternography in the evaluation of a patient with a cerebrospinal fluid leak.